Cs2AgBiBr6 and related Halide double perovskite porous single crystals - Maurya Sandeep Pradeepkumar; Aruchamy Kathirvel; Sayan Ghosh; Chandran Sudakar (Scientific Reports)
Abstract The utilization of single crystals is exponentially growing in optoelectronic devices due to their exceptional benefits, including high phase purity and the absence of grain boundaries. However, achieving single crystals with a porous structure poses significant challenges. In this study, we present a method for fabricating porous single crystals (porous-SC) of Cs2AgBiBr6 and related halide double perovskites using an infrared-assisted spin coating technique. The porous-SC are formed through a non-classical crystallization process, where oriented crystallographic platelets assemble into porous-SC clusters and merge to create iso-oriented single crystalline building blocks, with pore regions primarily located in the gaps between the platelets. Large porous square-shaped Cs2AgBiBr6 halide double perovskite (HDP) single crystals with lateral dimension ~ 10 to 50 μm and few µm thickness are realized with preferred orientation along {h00} on the FTO substrate upon subsequent spin-coating of layers. Analysis using angle-resolved polarized Raman spectroscopy, X-ray diffraction and transmission electron microscopy confirms the formation of single crystals of Cs2AgBiBr6. Further, to get a uniform coating of highly interconnected porous-SC clusters, wiping method under IR illumination is employed. Solar cell devices fabricated from these porous-SCs perform better with JSC =1.40 mA/cm2, VOC=1.04 V and η = 0.86% than the conventional polycrystalline thin films with JSC = 0.55 mA/cm2, VOC=0.94 V and η = 0.28%. Cs2AgBiBr6 porous-SC shows potential for a wide range of optoelectronic and photoelectrochemical applications.